(untitled) (Dhaka University Journal of Biological Sciences, 2018)
The effect of waterlogging (about 2 cm depth for 14 days) on anatomical structure in jute (Corchorus capsularis L. cv. D-154) plants grown in sand culture experiment was studied. Waterlogging resulted in the development of adventitious root, aerenchyma in the cortex of the stem. It also caused a decrease in vascular area as well as size of the vessels having smaller cavity in the root, stem and leaves. Pith area was found to increase in stem under waterlogging condition. Reduced number and closed stomata were found under waterlogging condition. Dhaka Univ. J. Biol. Sci. 27(2): 213-219, 2018 (July)